Structural and biochemical studies of cysteine-rich domains in morphogen signalling - Griffiths, S (2016)
Cell-to-cell communication is vital to the morphogenesis and homeostasis of multicellular organisms and is linked to a variety of diseases. Extracellular Cysteine-Rich Domains (CRDs) are involved in the control of fundamental signalling pathways, mediating crucial interactions with protein and small molecule ligands. The localisation of extracellular ligands and receptors is regulated by the cell surface glycosaminoglycan (GAG) layer. In this thesis, structural and biochemical methods have been used to characterise two multi-domain proteins containing CRDs – HHIP and ROR2. In Chapter 3, the process of structure solution of the HHIP N-terminal CRD (HHIP-N) by Sulphur-SAD phasing techniques is described. HHIP-N is a novel CRD, with implications for small molecule binding present. Chapter 4 concerns the study of the regulation of HHIP secretion and its interaction with GAGs. Discrete GAG-binding motifs are found on the surfaces of HHIP-N and the C-terminal region of HHIP (HHIP-C). Structural studies with GAGs enabled snapshots of cell surface-bound states. Interactions were dissected using cellular assays and GAG-binding experiments. In addition, the dynamics of HHIP oligomerisation were analysed using solution scattering and ultracentrifugation techniques. Work in this chapter represents a complex mode of HHIP assembly regulated by GAGs. In chapter 5, structural and biophysical studies of ROR2 were performed. A structure of the ROR2 CRD with its C-terminal Kringle domain was determined. The structure forms a potentially stable structural unit with a marked inter-domain interface. The CRD structure is distinct from related CRDs and suggests that it cannot directly bind Wnt proteins. This was complemented by biophysical and cellular assays. In summary, the CRD is a fold found in two unrelated signalling pathways tied to a number of diseases and its role in multi-domain protein architectures has been characterised within this thesis. CRDs are involved in a wide range of interactions and these are essential for the precise regulation of signalling pathway activation.